Development of E-Module SETS for Global Warming Using Carbon Sequestration Potential of Coastal Vegetation at Pantai Panjang Bengkulu - Melda Nuari Handini; Aceng Ruyani; Iwan Setiawan; M. Lutfi Firdaus; Henny Johan (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
Increasing issues of global warming and coastal environmental degradation require science learning that is able to connect scientific concepts with real environmental conditions surrounding students. This study aimed to develop an E-Module based on Science, Environment, Technology, and Society (SETS) through the analysis of the carbon sequestration potential of Bengkulu coastal vegetation as a learning medium for global warming materials. This study employed a Research and Development (R&D) method using the ADDIE model, which consisted of analysis, design, development, implementation, and evaluation stages. The results showed that the SETS E-Module achieved a “Very Valid” category with a total score of 93.18%. Teacher responses obtained a total score of 77,88% with the category of “Good Category”, while student responses reached 88,12% indicating that the E-Module was feasible for use in science learning. The developed E-Module was able to connect scientific concepts with real environmental conditions through the context of Bengkulu coastal vegetation, thereby supporting more contextual and meaningful learning.